2014
DOI: 10.1590/1678-4499.0124
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria induces resistance against Fusarium wilt of tomato by increasing the activity of defense enzymes

Abstract: Fusarium wilt, caused by Fusarium oxysporum f.sp. lycopersici (Fol), is one of the most important diseases that affect tomato yield worldwide. This study investigated the potential of three antagonists, Streptomyces setonii (UFV 618), Bacillus cereus (UFV 592) and Serratia marcescens (UFV 252), and as positive control the hormone jasmonic acid (JA), to reduce Fusarium wilt symptoms and to potentiate the defense enzymes in the stem tissues of tomato plants infected by Fol. The seeds were microbiolized with each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…JA is a phytohormone directly involved in the plant defense responses against stress, and used as a stress indicator. Choudhary (2011) and Ferraz et al (2014) reported that the application of biotic inducers able to stimulate LOX activity, contributed to the resistance of tomato plants against Fusarium sp., and also in soybean plants against Macrophomina phaseolina. In both cases, the disease control was attributed to the activation of JA pathway.…”
Section: Characmentioning
confidence: 99%
“…JA is a phytohormone directly involved in the plant defense responses against stress, and used as a stress indicator. Choudhary (2011) and Ferraz et al (2014) reported that the application of biotic inducers able to stimulate LOX activity, contributed to the resistance of tomato plants against Fusarium sp., and also in soybean plants against Macrophomina phaseolina. In both cases, the disease control was attributed to the activation of JA pathway.…”
Section: Characmentioning
confidence: 99%
“…Table 2. Analysis of variance of the effects of treatments (antagonists UFV252, UFV592 and UFV618; jasmonic acid and control) and evaluation times for peroxidase (POX), polyphenoloxidase (PPO), β-1,3-glucanase (GLU), chitinase (CHI), phenylalanine ammonia-lyase (PAL) and lipoxygenase (LOX) activities and malonic aldehyde (MDA) concentration mechanisms of PGPR revealed that several strains protect plants from pathogen attack through an increase in POX activity (Ferraz et al, 2014;Ganeshamoorthi et al, 2008;Vanitha & Umesha, 2011). This enzyme is important for the lignification of plant tissues, and lignin precursors exhibit antimicrobial activity (Ride, 1975).…”
Section: Resultsmentioning
confidence: 99%
“…The antagonists UFV252, UFV592, and UFV618 were selected from a universe of 635 bacterial isolates that promote biocontrol of Fusarium wilt (Ferraz et al, 2014), bacterial spot and early blight and in tomato plants. The antagonists were identified as Serratia marcescens (UFV252), Bacillus cereus (UFV592) and Streptomyces setonii (UFV618) by sequencing the 16S rDNA fragment, with the following numbers deposited in GenBank: KM463767, KM463766 and KM 463768, respectively.…”
Section: Source Of Xg and Antagonists Cultivation And Preservationmentioning
confidence: 99%
See 1 more Smart Citation
“…358 were reported to reduce Fusarium wilt on cucumber plants (Singh et al, 1999). Other study reported the potential of three antagonists, Streptomyces setonii, Bacillus cereus, and Serratia marcescens to reduce Fusarium wilt symptoms in the stem of tomato plants by F.oxysporum (Ferraz et al, 2014). Other factor besides hydrolytic enzymes produced by antagonistic bacteria in reducing Fusarium wilt were siderophores, cyanide, and antibiotics (Cantelan et al, 1999).…”
Section: In Vivo Antagonism Of Two Selected Antagonistic Bacterial Ismentioning
confidence: 99%